Bibliometric Analysis and Data Visualization: Life Cycle Assessment in Waste Management in the Textile Industry - Febian, Tiara; Mansur, Agus (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2025)
This study aims to analyze the development of literature on the application of Life Cycle Assessment (LCA) in textile waste management through a bibliometric approach using the Scopus database for the period 2013–2024. The analysis employed VOSviewer to map publication trends, keywords, citations, and authorship collaborations. The findings reveal a significant increase in the number of publications since 2014, peaking at 298 in 2024 before declining to 138 in 2025. Publication distribution is dominated by the journal Sustainability (Switzerland) with 106 articles, followed by Polymers and Materials. The most cited article received 650 citations, focusing on the impacts of COVID-19 on the global economy and opportunities for circular economy strategies. Thematically, research shifted from conceptual studies (2010–2015) toward technical solutions such as fiber recycling, microplastic pollution, and nanomaterials (2016–2020), then advanced to circular fashion, eco-design, and sustainable material innovations (2021–2025). Future trends (2026–2030) are projected to emphasize the digitalization of LCA through AI, big data, blockchain, and textile industry decarbonization strategies. This study offers both theoretical and practical contributions by enriching sustainability literature and serving as a strategic reference for policy development and the implementation of environmentally sustainable practices in the textile industry. Keywords: Bibliometrics, Circular Economy, Textile Industry, Life Cycle Assessment (LCA), Sustainability